Research progress of femoral head necrosis in HIV-infected patients - Youhan Yang; Futao Ke; Zhengqi Pan; Liaobin Chen (Annals of Medicine)
As life expectancy among patients infected with the human immunodeficiency virus (HIV) increases, a growing number of complications have been observed. This population displays an elevated risk of ischemic necrosis of the femoral head in comparison to the general population, which may be attributed to HIV infection, antiretroviral medication use, and hormone application. Patients infected with the human immunodeficiency virus (HIV) who also have necrosis of the femoral head tend to present at an earlier age, with a rapid disease progression and a high incidence of bilateral onset. Magnetic resonance imaging (MRI) facilitates the early diagnosis of the condition, and the recommended treatment is total hip arthroplasty. Currently, the most prevalent treatment modality is total hip arthroplasty. This can effectively prevent occupational exposure when the surgery is performed in accordance with the HIV infection control guidelines. Furthermore, the surgical procedure is more time-consuming than that performed on patients without HIV. The postoperative quality of life of patients is markedly enhanced, and there are no reports of surgical complications. The precise mechanism underlying femoral head necrosis in HIV-infected patients remains unclear. Potential contributing factors have been identified, including systemic immune response, inflammatory response, local microenvironmental changes in the femoral head, and the unique anatomical structure of the femoral head, among others. A more profound comprehension of the disease’s pathogenesis may facilitate the implementation of early prevention and treatment strategies, as well as the development of alternative conservative therapeutic options. This represents a promising avenue for future research. The present article reviews the epidemiological study of HIV-infected patients with osteonecrosis of the femoral head, local changes of the femoral head, possible mechanisms of osteonecrosis of the femoral head, occupational exposure during treatment, and surgical efficacy. The aim is to provide insights that can inform the diagnosis, prevention, treatment, and mechanism of this condition.